Mechanism Focus of Volcanic Type A Earthquake at Mount Semeru, East Java - Indonesia - Kartika Andryana; Sukir Maryanto; Adi Susilo; Hetty Triastuti (Natural B, Journal of Health and Environmental Sciences, 2011)
Study of the focal mechanisms of A-Type Volcanic earthquake (VA) Semeru has been done to know the volcanic activity in more detail, until the information about the magma migration process. The study began with the selection of seismic events that has a clear appearance, continued with the conversion value in the instrument readings and the amplitude correction which includes the correction of propagation effect and local effect. Hypocenter distribution showed that the epicenter was dominant in the northwest direction, relative to the central volcano, with a depth between 1-13 km. Interpretation of the hypocenter distribution, supported by past research as well as geological information around, gave initial estimates that there was a column of magma flow that leads from the northwest to the center of the crater. VA study of earthquake focal mechanism illustrate that the dominant type of normal fault occurs at the peak of eruption, and would change to reverse fault after the activity dropped to normal. From the research, VA earthquake in G. Semeru could be classified into two types: deep VA (VAD) with a depth range of more than 6 km and the shallow VA (VAS), with a depth of 1-6 km.